"Fat Kids Are Adorable": The Experiences of Mothers Caring for Overweight Children in Indonesia. (29th March 2019) - Suprawoto, Dina Nurpita; Hayati, Happy; Rachmawati, Imami Nur; Wanda, Dessie
ABSTRACT: This study aims to explore mothers' experiences in caring for overweight children under five years of age. This study used a descriptive phenomenology approach, with in-depth interviews with ten mothers who had overweight children under five years of age (2–5 years) selected by purposive sampling. The data was then analyzed using thematic analysis based on Collaizi's approach. This study produced eight themes illustrating that mothers were not only unaware of the children's overweight condition, but even felt more pleased to have overweight kids. This caused mothers not to give the optimum effort in limiting their children's food intake. The low awareness mothers had towards their children's overweight condition indicated the need for an intervention program that focuses on overweight children under five years of age to empower the family and increase family awareness in managing obesity early.